2022
DOI: 10.25134/erjee.v10i2.6260
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Students’ Learning Styles and the Eleventh Grade Students’ Speaking Ability at Sma N 4 Palembang

Abstract: The objective of this study was to find out whether or not there was a significant correlation of learning style and the eleventh grade students' speaking ability. In this study, the population was ten students the eleventh grade students of SMA N 4 Palembang. The sample of this study, the researcher used purposive sampling technique. In order to collect the data, in this study used interviews and an oral test from virtual classes. Analyze the data, the researcher used Pearson Product Moment Correlation Coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…One of the factors determining the success of any educational activity is the principle. Rahayu (2012) conducted research, and the findings indicate that teacher performance is influenced by academic credentials. Simbolon's research from ( 2012) with the study's findings demonstrated that professional and academic competencies both had an impact on job success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the factors determining the success of any educational activity is the principle. Rahayu (2012) conducted research, and the findings indicate that teacher performance is influenced by academic credentials. Simbolon's research from ( 2012) with the study's findings demonstrated that professional and academic competencies both had an impact on job success.…”
Section: Literature Reviewmentioning
confidence: 99%